2020
DOI: 10.1038/s41598-020-73731-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium citrate on the structure and microbial community composition of an early-stage multispecies biofilm model

Abstract: In recent years, most biofilm studies have focused on fundamental investigations using multispecies biofilm models developed preferentially in simulated naturally occurring low-nutrient medium than in artificial nutrient-rich medium. Because biofilm development under low-nutrient growth media is slow, natural media are often supplemented with an additional carbon source to increase the rate of biofilm formation. However, there are knowledge gaps in interpreting the effects of such supplementation on the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…S3 and S4). The observed biofilm microbial composition in columns is a result of changes to the inoculum composition and the strains’ relative ability to grow in our nutrient-supplemented media, since nutrient load can influence the microbial composition of biofilm community by promoting the growth or detachment of different species in biofilms ( 48 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…S3 and S4). The observed biofilm microbial composition in columns is a result of changes to the inoculum composition and the strains’ relative ability to grow in our nutrient-supplemented media, since nutrient load can influence the microbial composition of biofilm community by promoting the growth or detachment of different species in biofilms ( 48 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Yao et al (2020) reported that sodium citrate significantly affected the microbial community and the 3D structure of early-stage multispecies biofilms. 43 Similarly, multiple studies have reported that sodium citrate inhibits the growth of C. albicans, Staphylococcus aureus, Escherichia coli, S. epidermidis, and P. aeruginosa biofilms. 30,31,44−47 Our results showed that biofilm removal significantly increases with increased sodium citrate concentration for both single and multispecies biofilm.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies support our result for well-plate multispecies biofilms. Yao et al (2020) reported that sodium citrate significantly affected the microbial community and the 3D structure of early-stage multispecies biofilms . Similarly, multiple studies have reported that sodium citrate inhibits the growth of C.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the addition of an organic carbon source can increase the biovolume, thickness, and roughness of biofilms under low nutrient conditions. Preference of species for an organic carbon source can influence the microbial network dynamics in biofilms; for instance, the addition of citrate increased coexclusion interactions of Proteobacteria with other phyla and benefited the promoting effect of Actinobacteria on the cohesiveness of the biofilm (Y. Yao et al., 2020). Temperature is an important environmental factor, and low temperatures are usually used to delay the growth of spoilage bacteria to preserve food, especially during the storage phase.…”
Section: Formation Of Multispecies Biofilmsmentioning
confidence: 99%